The Suitability of History Textbook Activities for 5th–8th Grades for Developing Pupils’ Achievements in the Subject of History - Jašinauskas, Linas; Žiburytė, Rasa (Pedagogika, 2016)
After restoring Independence in Lithuania, there has not been a separate research carried out which would contain an in-depth analysis of the quality of activities presented in history textbooks used in general education schools. Therefore, the following research problem is raised in this article: whether the activities presented in the history textbooks for 5th–8th grades that are currently in use in Lithuanian general education schools are suitable for developing the achievements in history subject which are defined in the General Curriculum Framework. The aim of this study is to investigate the suitability of history textbook activities for 5th–8th grades for developing pupils‘ achievements delineated in the General Curriculum Framework 2008. To reach this aim the following objectives were raised: 1) to discuss the key achievements in history subject as well as the requirements for history learning process that are highlighted in scientific literature and educational programmes; 2) to reveal the role of a textbook and its activities / activities system for improving pupils’ achievements in accordance to Lithuanian education documents and scientific literature; 3) to analyse the suitability of history textbook activities for 5th–8th grades for improving pupils’ knowledge and skills delineated in the General Curriculum Framework for Basic Education 2008 for the subject of history. Methods of research: analysis of education documents and scientific literature, analysis of textbook content. Data of the analysis revealed that more than half of the tasks in the investigated history textbooks for 5th–8th grades require from pupils knowledge and understanding of historical figures, events or cases depicted in a textbook. Fewer than a quarter of the analysed history textbook activities are designed to developing pupils’ ability to put knowledge into practice. Very few tasks presented in textbooks are intended for developing the capacity for more complicated reasoning. Whilst analysing the adaptation of activities in history textbooks for 5th–8th grades for developing pupils‘ competencies in the subject, it became clear that the activities are only partially suitable for developing the competencies delineated in the General Curriculum Framework. The greater part of tasks is designed for developing an understanding of historical evolution and ability to engage in historical analysis and interpretation. Only 4.3 percent of tasks induce the pupils to develop an ability to orientate in historical time and space. The analysed textbooks contain few activities that would motivate pupils to take an integral approach towards Lithuanian and world history.